Implementation of Regenerative Technologies for Sustainable and Net-Zero Rice Farming in Adapting to Climate Change in Indonesian Coastal Areas - Simarmata Tualar; Irwandhi; Khumairah Fiqriah; Hibatullah Fairus; Ambarita Debora; Herdiyantoro Diyan; Kamaludin Nadia; Nurbaity Anne; Adinata Kustiwa; Stöber Silke (BIO Web of Conferences)
Success in achieving Indonesia’s dream of food security is faced with various significant challenges in line with climate change, which impacts sea level rise, salinity intrusion, and unpredictable weather patterns. These factors cause a decrease in rice production and salinization of rice fields in coastal areas. Regenerative technologies present a viable solution for achieving sustainable, net-zero rice farming (NZF) while enhancing resilience to climate change. This study comprehensively assesses the implementation of these technologies in Indonesian coastal regions. A bibliometric analysis and a summary of innovative agricultural methods, such as the System of Organic-Based Aerobic Rice Intensification (SOBARI), also known as IPATBO, highlight their effectiveness in improving rice yields and soil health. Results from regenerative technology demonstrations (2007–2024) show improved soil health and increased fertilizer and water efficiency, reducing inorganic inputs by 25–50% and water use by 30–40% while raising rice productivity by 25–50%. Adopting eco-friendly practices, including algal biofertilizers and compost, has further enhanced soil health. In addition, the practice of the NZF system in Indonesia will support Indonesia’s targets in reducing greenhouse gas emissions and carbon absorption.